PERSEPSI PEMBACA TERHADAP PERGANTIAN KATA KORUPTOR DI MEDIA MASSA (STUDI KASUS PADA PIKIRAN RAKYAT MEDIA NETWORK) - Baskhara, Ida Bagus Aditya; Gelgel, Ni Made Ras Amanda; Pradipta, Ade Devia; Damasemil, Calvin (E-Jurnal Medium, 2023)
Pikiran Rakyat Media Network (PRMN) is part of Pikiran-Rakyat.com which was created out of concern over the increasing number of unemployed in Indonesia. Pikiran Rakyat Media Network (PRMN) is here to make a real contribution. PRMN builds a digital media ecosystem that is dedicated to the independence of Indonesian youth, especially in the field of text and video-based content creators. PRMN prepares technology, infrastructure, training, mentoring, to a business plan, to give birth to new entrepreneurs in the field of digital media (Mediapreneur). On August 29, 2021, PRMN came up with the idea that it would start changing the word corrupt in its reporting to thieves, robbers, and looting people’s money. This study uses a quantitative descriptive research method that aims to see the reader’s perception of the word corruption carried out by PRMN. The results of this study indicate that the reader’s perception of the word corruptor gets positive results. Most of the readers also stated that they supported the PRMN’s replacement of the word corruptor.   KeyWord : Perception, Substitution, Word, Corrupt, PRMN